1998
DOI: 10.1046/j.1440-1754.1998.00272.x
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of two methods for collection of sterile urine in neonates

Abstract: In this small randomized controlled trial urethral catheterization offered no significant advantage over SPA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 14 publications
2
22
0
Order By: Relevance
“…In addition, all boys in our study were uncircumcised, but in Kozer's study all the boys were circumcised. Finding the urethral meatus by retraction of the prepuce may be more difficult in smaller infants and in uncircumcised boys, thus making TUC more difficult [1, 6, 7]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, all boys in our study were uncircumcised, but in Kozer's study all the boys were circumcised. Finding the urethral meatus by retraction of the prepuce may be more difficult in smaller infants and in uncircumcised boys, thus making TUC more difficult [1, 6, 7]. …”
Section: Discussionmentioning
confidence: 99%
“…SPA is considered the “gold standard” [3] technique for sterile urine collection in neonates [1, 3, 4], but TUC has an acceptable sensitivity of 95% and a specificity of 99% if colony counts greater than 1000 CFU/mL are considered positive [3]. Neither method always successfully collects a sufficient volume of urine [1, 57], and both methods are invasive and painful [1, 5]. …”
Section: Introductionmentioning
confidence: 99%
“…From the three studies which directly compared SPA and UC samples, two1 3 showed no significant increase in sample contamination from catheters compared to SPA, whilst the third study2 had 22% contamination in UC samples and 0% in SPA. Simply grouping the three studies together increased the numbers in each group and, using Fisher’s exact test, shows catheter samples are significantly more likely to be contaminated than SPA samples (p = 0.002).…”
Section: Commentarymentioning
confidence: 96%
“…For example, the studies varied in their use of cleaning agent. Austin et al 2 cleaned with saline before catheter samples but alcohol before SPA, whereas Tobiansky et al 1 used the same cleaning method before both methods (aqueous chlorhexidine and iodine). It is known that cleaning with soap and water before collecting midstream clean catch samples reduces the contamination rate in toilet-trained populations,19 but there have been no studies examining the effect of cleaning with saline or sterile water versus chlorhexidine or iodine.…”
Section: Commentarymentioning
confidence: 99%
“…Per the 1999 American Academy of Pediatrics UTI guideline, 10 catheterization has a sensitivity of 95% and a specificity of 99% compared with SPA, with catheterization also more likely to lead to contamination. [11][12][13][14] Although SPA would thus appear to be the gold standard, 2 additional operational factors were discovered when considering SPA to diagnose UTI. Urine catheterization is performed by nursing, whereas SPA is performed by physicians.…”
Section: Operational Factors/implementabilitymentioning
confidence: 99%